Fabrication and Photovoltaic Effect of CdS/Silicon Nanopillars Heterojunction Solar Cell. Issue 15 (30th September 2016) - Liu, Jing; Yi, Futing; Wang, Bo; Zhang, Tianchong; Wang, Yuting; Zhou, Yue
Abstract: A 200 nm thickness layer of Cadmium sulfide (CdS) film covers on the silicon nanopillars surface to heterojunction solar cell. The nanopillars with the large surface ratio can increase the heterojunction surface and the light absorption, which can improve the photovoltaic performance of solar cell. Silicon nanopillars are fabricated by Cesium Chloride self‐assembly lithography and inductively coupled plasma dry etching as substrate. CdS film covers the silicon nanopillars surface by the RF magnetron sputtering using CdS ceramic target. The X‐ray diffraction patterns of the nanopillar and planar substrates after CdS film covering indicate that all the deposited films are crystal. The nanopillars wafer has lower reflectance than the planar one both before and after the CdS film covering for the wavelength ranging from 350 to 1050 nm. With this method, the nanopillar based CdS/Silicon heterojunction solar cell has the better photovoltaic performance than the planar one. The Jsc increases from 7.12 to 13.92 mA/cm 2 and the energy conversion efficiency increases from 1.32 % to 1.83 %. The large surface ratio nanopillars might be a potential substrate for high efficiency heterojunction solar cell. Abstract : A 200 nm thickness layer of Cadmium sulfide (CdS) film covers on the silicon nanopillars surface to heterojunction solar cell. The nanopillars with the large surface ratio can increase the heterojunction surface and the light absorption, which can improve the photovoltaic performance of solar cell. The nanopillar based CdS/Silicon heterojunction solar cell has the better photovoltaic performance than the planar one. The Jsc increases from 7.12 to 13.92 mA/cm 2 and the energy conversion efficiency increases from 1.32 % to 1.83 %.